Constructive Law Enforcement through Interlocutory Injunction: An Effort to Achieve Procedural Justice - Oki Muji Astuti (Budapest International Research and Critics University, 2022)
An interlocutory injunction is a decision that is temporary before examining the subject matter that was handed down before the final decision and can end the examination of the case in court. that based on Article 156 paragraph (1) of the Criminal Code states that there are several reasons that the defendant or his legal advisor can submit to the exception or objection of the indictment being unacceptable, including: What is being charged against the defendant is not a crime or violation criminal offense or violation but is included in a civil dispute, but in practice, the Panel of Judges in passing an Interim Decision in a criminal case continues the examination of the case based on the Public Prosecutor's Indictment and the Exception of the Defendant's Legal Counsel is not accepted against the object and subject matter of the same case which has been decided legally. Civil law and has permanent legal force at the level of the Supreme Court. The method used in this study is a normative juridical research method using a statutory approach, a case approach and a conceptual approach. The results of this study are expected that the Panel of Judges in giving/imposing an interim decision on a criminal case against the object and subject matter of the same case which has been decided in a civil manner and has permanent legal force, should look at the facts in the trial and the applicable rules, namely the Book of Law. -Law on the Criminal Procedure Code (KUHAP), so that it can give/impress the correct interlocutory decision.